The Influence of Islamic Work Ethic, Spiritual Suggestion, and Work Environment on Employee Performance at Bumdes with the Mediation of Device Synergy at Bumdes Nawamitra Mandiri, Purbalingga Regency - Huda, Fatkhilil (Indonesian Journal of Islamic Business and Economics (IJIBE), 2025)
This research is a survey research on BUMDES Employees in Pengadegan District, Purbalingga Regency. This research is entitled "The Influence of Islamic Work Ethic, Spiritual Suggestions and Work Environment on the Performance of Bumdes Employees Mediated by Device Synergy at Bumdes Nawamitra Mandiri Purbalingga Regency" The aim of this research is to determine the influence of Islamic Work Ethic, Spiritual Suggestions and Work Environment between Devices at Bumdes Nawamitra Mandiri Purbalingga Regency. The population in this study were employees of BUMDeis Nawamiitra Mandiirii in the Regency of Purbalingga Beiseirta government officials. The number of respondents taken in this research was 22 respondents. The purposive sampling method was used to determine respondents. Based on the results of research and data analysis using SEM (Structural Equation Modeling) it shows that: (1) Islamic work ethic influences device synergy, (2) Islamic work ethic influences employee performance, (3) Spiritual suggestions influence device synergy, (4 ) Spiritual suggestions influence employee performance, (5) Work environment influences device synergy, (6) Work environment influences employee performance, (7) Islamic work ethic influences employee performance mediated by device synergy, (8) Spiritual suggestions influence employee performance. employee performance mediated by device synergy, (9) The work environment influences employee performance mediated by device synergy. This research examines and expands the theoretical model that connects the Islamic work ethic and employee performance through the synergy of tools as mediation. Although some hypotheses were not supported, this research can provide a broad understanding of these relationships.